“LA NO OBLIGATORIEDAD DE LAS VISITAS POR PARTE DE LAS DIRECCIONES REGIONALES DEL TRABAJO, VULNERAN LOS DERECHOS DE LOS TRABAJADORES EN EL SECTOR RURAL” - Erazo Merino, Johnny David (2021)
This research work entitled "The non-obligation of visits by regional labour directives violates the rights of workers in the rural sector" includes a conceptual, doctrinal and legal study, in addition to the Treaty on Human Rights (ILO Conventions 81 and 129), and Comparative Law; different methods and techniques were also applied, to verify the fulfilment of the objectives planted in the thesis project, and their respective hypothesis contrast. The investigation is the result of the analysis of the problems that exist around the violation of workers' rights due to the non-obligation of visits by the Regional Labour Directives, focusing on the rural sector; this because there is no policy that obliges an institution to carry out mandatory and regular inspections (visits) of work, since the Labour Code (2015) in article 5 Article 542, one of the powers of the Regional Labour Directions is: "Visit factories,workshops, establishments, buildings of premises intended for work and workers' dwellings whenever deemed appropriate or when companies or workers so request (p.59)" , leaving free will to carry out these visits, the resulting in no guarantee that labour rights are being respected. And as was evident in the results obtained from the survey and interview, where it was determined that the rights of the worker are violated, this because there is no effective control by the Regional Labour Directions, through the Labour Inspectorates, for verification of compliance with the different regulations, thus allowing the rural worker to be violated; and to date there is no solution to this. For this reason, the need arises to submit a Proposal for Reform to the Labour Code in article 5 Article 542, as follows: "Visit factories, workshops, establishments, buildings of premises intended for work and workers' homes, on a mandatory and regular basis every 90 days or when companies or workers request it; in addition, an exclusive register of rural workers will be keeping in place", a reform that will allow the rights of workers, especially in the rural sector, not to continue to be infringed.